Survival prediction of hepatocellular carcinoma by measuring the extracellular volume fraction with single-phase contrast-enhanced dual-energy CT imaging - Chen, Yan; Shi, Kexin; Li, Zhen; Wang, Huixia; Liu, Nana; Zhan, Pengchao; Liu, Xing; Shang, Bo; Hou, Ping; Gao, Jianbo; Lyu, Peijie (Frontiers in Oncology, 2023)
To investigate the value of quantified extracellular volume fraction (fECV) derived from dual-energy CT (DECT) for predicting the survival outcomes of patients with hepatocellular carcinoma (HCC) after transarterial chemoembolization (TACE).Sixty-three patients with HCC who underwent DECT before treatment were retrospectively included. 70 keV virtual monochromatic images (VMI) and iodine density images (IDI) during the equilibrium phase (EP) were generated. The tumor VMI-fECV and IDI-fECV were measured and calculated on the whole tumor (Whole) and maximum enhancement of the tumor (Maximum), respectively. Univariate and multivariate Cox models were used to evaluate the effects of clinical and imaging predictors on overall survival (OS) and progression-free survival (PFS).The correlation between tumor VMI-fECV and IDI-fECV was strong (both p < 0.001). The Bland-Altman plot between VMI-fECV and IDI-fECV showed a bias of 5.16% for the Whole and 6.89% for the Maximum modalities respectively. Increasing tumor VMI-fECV and IDI-fECV were positively related to the effects on OS and PFS (both p < 0.05). The tumor IDI-fECV-Maximum was the only congruent independent predictor in patients with HCC after TACE in the multivariate analysis on OS (p = 0.000) and PFS (p = 0.028). Patients with higher IDI-fECV-Maximum values had better survival rates above the optimal cutoff values, which were 35.42 % for overall survival (OS) and 29.37% for progression-free survival (PFS).The quantified fECV determined by the equilibrium-phase contrast-enhanced DECT can potentially predict the survival outcomes of patients with HCC following TACE treatment.